Behind Intermediary Performance in Export Trade: Transactions, Agents, and Resources - Peng, Mike W.; York, Anne S. (Journal of International Business Studies, 2001)
Integrating transaction cost, agency, and resource-based theories, this study extends the work of Peng and Ilinitch (1998) by undertaking the first empirical efforts to explore the determinants of export intermediary performance. We suggest that given the transaction cost constraints and principal-agent conflicts, export intermediaries' performance depends on their possession of valuable, unique, and hard-to-imitate resources which help minimize their clients' transaction and agency costs. Survey results from 166 firms largely support our hypotheses.